Performance analysis of a single-cylinder type steam turbine with a capacity of 3.5 mw using enthalpy drop method - Bagus Adi Saputra; Nurato Nurato (Universitas Mercu Buana, 2023)
The performance capability of the steam turbine under factory conditions will experience changes that can be caused by operating or environmental factors. Therefore, it is necessary to analyze the performance of the steam turbine during the actual condition so that it can be compared with the performance of the steam turbine from the manufacturer using mass and energy balance equations on HP heater #1 and deaerators and iteration methods. The research was conducted by looking at the phenomena that occur in the steam turbine using mathematical models and theories when the unit operates according to the heat balance design parameters. Feedwater flow from the calculation of the iteration method based on the equation of the water heater obtained a value of 17,961.58 kg/h. The performance steam turbine experienced a decrease in efficiency with a value for isentropic efficiency of 72.73% down 6.54% from the design value of 79.27% and thermal efficiency of 26.88% down 1.75% from the design value of 28.64%. Meanwhile, the steam rate value of 5.03 kg/kWh increased by 0.44 kg/kWh from the design value of 4.59 kg/kWh, and the turbine heat rate of 3198.83 kcal/kWh, an increase of 196.08 kcal/kWh from the design value of 3002.75 kcal/kWh.